Cr2AlC derived two-dimensional carbide material and preparation method thereof
By using salts such as copper chloride and sodium chloride and potassium chloride for high-temperature melt etching, the problem of difficulty in peeling Cr2AlC materials is solved, and the preparation of efficient peeling of two-dimensional carbide materials is achieved, suitable for supercapacitor electrodes Material, simple process, safe and environmentally friendly.
Patent Information
- Application Number
- CN202411267978.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-17
AI Technical Summary
Cr2AlC materials are difficult to peel off into two-dimensional materials. Traditional etching methods lead to dissolving or incomplete removal of Cr and Al, and there are problems with peeling complexity and stability.
Copper chloride is used as an etchant, combined with sodium chloride and potassium chloride salt for high-temperature melt etching. The chemical potential difference between Cu2+/Cu and Al3+/Al is used to achieve efficient peeling of Cr2AlC to obtain porous two-dimensional carbides Material.
The obtained two-dimensional material is suitable for supercapacitor electrode materials. The steps are simple, green and safe, the peeling efficiency is high, and there is no need for secondary crushing and grinding. The surface ion type is simple and does not carry harmful F-.
Smart Images

Figure CN119143133A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of two-dimensional material preparation, and in particular relates to a Cr2AlC-derived two-dimensional carbide material and a preparation method thereof. The two-dimensional carbide material can be applied to supercapacitor electrode materials. Background Art
[0002] Due to the multifunctional properties and wide range of potential applications of two-dimensional materials, exfoliating three-dimensional bulk materials into corresponding two-dimensional layered materials has become an important method for researchers to obtain new materials with novel functional properties. In recent years, researchers have found that the microscopic chemical structure of MAX phase (M is a transition metal element, A is a main group element, and X is C or N) transition metal carbides is composed of alternating stacking of strongly chemically bonded MX layers and weakly chemically bonded A layer atoms to form a three-dimensional nano-laminated structure. Based on the difference in interlayer / intralayer forces, a new type of two-dimensional MXene material can be obtained by selectively removing the more active A layer atoms using chemical etching and exfoliation methods.
[0003] Compared with the parent MAX phase material, MXene materials not only increase the surface area but also adsorb a variety of active functional groups on the surface, and can be widely used in energy storage and conversion fields, such as batteries, supercapacitors, catalysis and hydrogen storage. According to the number of M layers in the MX layer in the composition structure of the MAX phase material, it is divided into 211 phase, 321 phase, 413 phase, 514 phase and 712 phase. At present, researchers have used fluoride salts such as HF, HCl+LiF or NH4HF2 as etchants to obtain derived two-dimensional MXene materials from various types of parent MAX phase materials, such as Ti2CT x 、V2CT x 、Ti3C2T x 、Nb4C3T x 、V4C3T x The stability and functionality of MXene two-dimensional materials are highly dependent on their parent MAX phase. The MAX phase materials corresponding to the above MXene materials have high bonding strength in the MX layer and still maintain strong structural stability in a chemical etching environment.
[0004] However, due to the strong chemical bonding between Cr and Al in the Cr2AlC MAX phase and the poor stability of Cr2C in aqueous solution, Cr2AlC stripping is difficult. For example, using HF to strip Cr2AlC causes Cr and Al to dissolve during the etching process and form fluoride salts; aqua regia and hydrogen peroxide are used as etchants to form oxides instead of selectively removing aluminum; electrochemical etching methods using hydrochloric acid as an etchant cannot completely remove Al even after long-term etching. In addition, Cr and Al have similar reactivity to HF and other strong acids / bases, rather than preferentially etching Al from Cr2AlC as in the stripping process of other MAX phase materials. Therefore, the stripping process of Cr2AlC is very complicated and still faces severe challenges. It is urgent to find an efficient stripping method. Summary of the invention
[0005] In view of the current problem that it is difficult to exfoliate Cr2AlC into a two-dimensional material, the present invention aims to provide a Cr2AlC-derived two-dimensional carbide material and a preparation method thereof. The method can achieve complete and efficient exfoliation of Cr2AlC, and the obtained new two-dimensional porous carbon material can be used as an electrode material in a supercapacitor.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] A Cr2AlC-derived two-dimensional carbide material, characterized in that the two-dimensional carbide material is obtained by high-temperature melt etching using Cr2AlC composed of transition metal chromium, metal aluminum and carbon as a matrix material, copper chloride as an etchant, mixed with sodium chloride salt and potassium chloride salt; the molecular formula of the two-dimensional carbide material is: Cr x C y T z , where 0 <x<2,0<y<1,0<z<2,T=Cl - , O 2- and OH - It has a hexagonal crystal structure and its microscopic morphology is like a multi-layer stacked accordion.
[0008] A method for preparing a novel Cr2AlC-derived two-dimensional carbide material comprises the following steps:
[0009] (1) Weighing three kinds of raw material powders, namely, Cr powder, Al powder and C powder, and encapsulating them in a ball milling jar in an argon environment in a glove box, and then mixing them evenly by ball milling in a planetary ball mill; manually grinding and mixing the mixed raw material powders with sodium chloride salt and potassium chloride salt in an agate mortar in the glove box, placing them in an alumina crucible, and placing them in a muffle furnace. Under the protection of inert gas, the crucible is heated to 1100-1300° C. at a heating rate of 5-10° C. / min, and sintered at high temperature for 1-3 h; cooling to room temperature with the furnace, centrifugally washing with deionized water for more than three times to remove sodium chloride and potassium chloride, and vacuum drying to obtain a Cr2AlC MAX phase powder material.
[0010] (2) Using the Cr2AlC MAX phase powder obtained in step (1) as the matrix material, weighing Cr2AlC, copper chloride salt, sodium chloride salt and potassium chloride salt, manually grinding and mixing in an agate mortar, placing them in an alumina crucible, placing them in a muffle furnace, heating them to 300° C. under the protection of flowing inert gas and keeping them warm for 30 min; then continuing to heat to high temperature for a period of time; cooling to room temperature after the reaction is completed, centrifuging and washing with deionized water for more than three times to remove excess copper chloride, sodium chloride and potassium chloride salt, and then centrifuging and washing with FeCl3 solution for three times to remove Cu 2+ The reduced Cu element is freeze-dried to obtain a two-dimensional carbide material.
[0011] Preferably, in step (1), the molar ratio of the raw material powders of Cr powder, Al powder and C powder to the sodium chloride salt and potassium chloride salt is 2:1-1.3:1:2:2.
[0012] Preferably, in step (2), the molar ratio of Cr2AlC to copper chloride, sodium chloride and potassium chloride is 1:1.5-6:1:1.
[0013] Preferably, in step (2), the heating rate at a temperature above 300° C. is 2 to 5° C. / min, the high reaction temperature is 600 to 700° C., and the reaction time is 3 to 9 hours.
[0014] Preferably, the concentration of the FeCl3 solution used in step (2) is 0.5 to 1 mol / L.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] (1) The present invention utilizes Cu 2+ / Cu and Al 3+ / Al chemical potential difference, the molten salt etching method is used to strip the difficult-to-strip Cr2AlC MAX phase into a two-dimensional material. Compared with the traditional strong acid and strong base etching environment such as HF, HCl+LiF, this method has simple steps, mild reaction, green and safe, low pollution, high stripping efficiency, simple surface ion types of the two-dimensional sheet, and does not carry F that is harmful to the electrochemical performance.- .
[0017] (2) The present invention first adopts a molten salt method to prepare a powdered Cr2AlC MAX phase matrix material. Compared with the conventional MAX phase preparation methods such as cold pressing mixed ceramic powder into sheets and then pressureless sintering or carbon-embedded pressureless sintering, the method is simple to operate, and the prepared Cr2AlC powder has a uniform particle size and a clean and pollution-free particle surface, and can be directly used for the next step of etching and peeling without secondary crushing and grinding. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Schematic diagram of the structural changes of Cr2AlC before and after peeling.
[0019] Figure 2 XRD comparison diagram of the physical phase before and after peeling of Example 1.
[0020] Figure 3 Comparison of particle micromorphology before and after peeling in Example 2.
[0021] Figure 4 Supercapacitor capacitance performance diagram of the material after stripping in Example 3. DETAILED DESCRIPTION
[0022] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0023] Example 1
[0024] Weigh 10g 200 mesh Cr powder, 5.71g 300 mesh Al powder and 2.31g 300 mesh C powder respectively, place them in a ball mill filled with zirconium oxide ball milling balls and inert gas Ar or N2, and mix the raw powders evenly with the help of a planetary ball mill. After mixing, the ceramic powder is manually mixed with 22.48g sodium chloride salt and 28.67g potassium chloride salt in an agate mortar in a glove box, then loaded into an alumina crucible, placed in a muffle furnace, heated at a heating rate of 10°C / min under inert gas protection, kept at 1200°C for 2h, cooled, washed with deionized water to remove sodium chloride and potassium chloride, and vacuum dried to obtain Cr2AlC MAX phase powder material.
[0025] The Cr2AlC MAX phase powder obtained in the above steps is used as the matrix material. First, 5g Cr2AlC, 8.95g copper chloride salt, 4.04g sodium chloride salt and 5.2g potassium chloride salt are weighed respectively, and they are manually ground and mixed in an agate mortar and placed in an alumina crucible. Then put it into a muffle furnace, heat it to 300℃ at a heating rate of 4℃ / min in a flowing inert gas and keep it warm for 30min. Then heat it to 600℃ at a heating rate of 5℃ / min and keep it warm for 3h. After cooling to room temperature, centrifuge and wash it with deionized water for more than three times to remove excess copper chloride, sodium chloride and potassium chloride salts, then centrifuge and wash it with 1mol / L FeCl3 solution three times, and freeze-dry it for 24h to obtain the Cr2AlC-derived two-dimensional carbide material.
[0026] The above-obtained materials were subjected to XRD testing, and the results were as follows: Figure 1 As shown in the figure, after CuCl2 is stripped, the diffraction peak originally belonging to the Cr2AlC matrix material basically disappears, and there is a significant Cu single substance diffraction peak. This is because Cu 2+ The Cu element is reduced to Cu using FeCl3 solution. 2+ After washing, a strong peak appears at around 2θ=3° in the XRD graph. By zooming in on the XRD local graph within 20°, it can be found that there is also a sharp peak at around 3° in the diffraction graph before removing the Cu element. Expand to At the same time, combined with the etching process of other MAX phase materials, it can be concluded that the Cr2AlC MAX phase is peeled off to generate a new type of two-dimensional material.
[0027] Example 2
[0028] Weigh 10g 200 mesh Cr powder, 6.23g 300 mesh Al powder and 2.31g 300 mesh C powder respectively, place them in a ball mill filled with zirconium oxide ball milling balls and inert gas Ar or N2, and mix the raw powders evenly with the help of a planetary ball mill. After mixing, the ceramic powder is manually mixed with 22.48g sodium chloride salt and 28.67g potassium chloride salt in an agate mortar in a glove box, then loaded into an alumina crucible, placed in a muffle furnace, heated at a heating rate of 10°C / min under inert gas protection, kept at 1200°C for 2h, cooled, washed with deionized water to remove sodium chloride and potassium chloride, and vacuum dried to obtain Cr2AlC MAX phase powder material.
[0029] The Cr2AlC MAX phase powder obtained in the above steps was used as the matrix material. First, 5g Cr2AlC, 17.88g copper chloride salt, 4.04g sodium chloride salt and 5.2g potassium chloride salt were weighed respectively, and they were manually ground and mixed in an agate mortar and placed in an alumina crucible. Then it was placed in a muffle furnace and heated to 300°C at a heating rate of 4°C / min in a flowing inert gas and kept warm for 30min. Then it was heated to 700°C at a heating rate of 5°C / min and kept warm for 3h. After cooling to room temperature, it was centrifuged and washed with deionized water for more than three times to remove excess copper chloride, sodium chloride and potassium chloride salts, and then centrifuged and washed three times with 1mol / L FeCl3 solution, and freeze-dried for 24h to obtain a Cr2AlC-derived two-dimensional carbide material.
[0030] The difference between Example 1 and Example 2 is that the quality of Al powder used in preparing the Cr2AlC MAX phase powder material is different. The melting point of Al is about 660°C. Part of Al is lost due to high temperature melting and volatilization. Therefore, the quality of Al raw material is increased in Example 2. In addition, in order to improve the etching rate, the quality of copper chloride etchant is increased in Example 2, and the reaction temperature is increased from 600°C in Example 1 to 700°C. From the comparison of the microscopic morphology of particles before and after peeling in Example 2, it can be seen that the surface of the Cr2AlC MAX phase matrix powder material presents a tightly stacked laminated morphology before peeling, and after peeling, the distance between the layers on the particle surface is greatly expanded, forming a multi-layer stacked accordion layered structure.
[0031] Example 3
[0032] Weigh 10g 200 mesh Cr powder, 6.23g 300 mesh Al powder and 2.31g 300 mesh C powder respectively, place them in a ball mill filled with zirconium oxide ball milling balls and inert gas Ar or N2, and mix the raw powders evenly with the help of a planetary ball mill. After mixing, the ceramic powder is manually mixed with 22.48g sodium chloride salt and 28.67g potassium chloride salt in an agate mortar in a glove box, then loaded into an alumina crucible, placed in a muffle furnace, heated at a heating rate of 10°C / min under inert gas protection, kept at 1200°C for 2h, cooled, washed with deionized water to remove sodium chloride and potassium chloride, and vacuum dried to obtain Cr2AlC MAX phase powder material.
[0033] The Cr2AlC MAX phase powder obtained in the above steps is used as the matrix material. First, 5g Cr2AlC, 17.88g copper chloride salt, 4.04g sodium chloride salt and 5.2g potassium chloride salt are weighed respectively, and they are manually ground and mixed in an agate mortar and placed in an alumina crucible. Then put it into a muffle furnace, heat it to 300°C at a heating rate of 2°C / min in a flowing inert gas and keep it warm for 30min. Then heat it to 650°C at a heating rate of 5°C / min and keep it warm for 6h. After cooling to room temperature, centrifuge and wash it with deionized water for more than three times to remove excess copper chloride, sodium chloride and potassium chloride salt, then centrifuge and wash it with 1mol / L FeCl3 solution three times, and freeze-dry it for 24h to obtain a Cr2AlC-derived two-dimensional carbide material. The two-dimensional carbide material obtained by peeling off in Example 3 above is made into an electrode, and its electrochemical performance in a supercapacitor is tested.
[0034] The difference between Example 3 and Example 2 is that, in order to further improve the stripping efficiency and control the microscopic morphology of the two-dimensional material, Example 3 further optimizes the stripping reaction conditions on the basis of Example 2, reduces the temperature rise in the low temperature section from 4°C / min in Example 2 to 2°C / min, reduces the reaction temperature from 700°C to 650°C, and extends the heat preservation time to 6h. The capacitance performance of the two-dimensional material obtained in Example 3 in the supercapacitor is further evaluated. Figure 3 The capacitance diagram shows that the two-dimensional material prepared by the present invention has a capacitance of 1Ag. -1 At a current density of 135F g -1 The capacitance can be used as electrode material for supercapacitors.
[0035] The above embodiments are only intended to illustrate the technical content of the present invention, rather than to limit the implementation methods of the present invention. Any technical extension or re-creation made according to the present invention is within the protection scope of the present invention.
Claims
1. A Cr2AlC-derived two-dimensional carbide material, characterized in that: The two-dimensional carbide material is obtained by high-temperature melt etching using Cr2AlC composed of transition metal chromium, main metal aluminum and carbon as the matrix material, copper chloride as the etchant, mixed with sodium chloride salt and potassium chloride salt; the molecular formula of the two-dimensional carbide material is: Cr x C y T z , where 0 <x<2,0<y<1,0<z<2,T=Cl - , O 2- and OH - It has a hexagonal crystal structure and its microscopic morphology is like a multi-layer stacked accordion.
2. The method for preparing a Cr2AlC-derived two-dimensional carbide material according to claim 1, characterized in that: The following steps are involved: (1) weighing three kinds of raw material powders, namely, Cr powder, Al powder and C powder, and encapsulating them in a ball milling jar in an argon environment in a glove box, and then mixing them evenly by ball milling with a planetary ball mill; manually grinding and mixing the mixed raw material powders with sodium chloride salt and potassium chloride salt in an agate mortar in the glove box, placing them in an alumina crucible, placing them in a muffle furnace, heating them to 1100-1300° C. at a heating rate of 5-10° C. / min under the protection of inert gas, and sintering them at high temperature for 1-3 h; cooling them to room temperature with the furnace, centrifugally washing them with deionized water for more than three times to remove sodium chloride and potassium chloride, and vacuum drying them to obtain Cr2AlC MAX phase powder material; (2) Using the Cr2AlC MAX phase powder obtained in step (1) as the matrix material, weighing Cr2AlC, copper chloride salt, sodium chloride salt and potassium chloride salt, manually grinding and mixing in an agate mortar, placing them in an alumina crucible, placing them in a muffle furnace, heating them to 300° C. under the protection of flowing inert gas and keeping them warm for 30 min; then continuing to heat to high temperature for a period of time; cooling to room temperature after the reaction is completed, centrifuging and washing with deionized water for more than three times to remove excess copper chloride, sodium chloride and potassium chloride salt, and then centrifuging and washing with FeCl3 solution for three times to remove Cu 2+ The reduced Cu element is freeze-dried to obtain a two-dimensional carbide material.
3. The method for preparing a Cr2AlC-derived two-dimensional carbide material according to claim 2, characterized in that: In the step (1), the molar ratio of the raw material powders of Cr powder, Al powder and C powder to the sodium chloride salt and potassium chloride salt is 2:1-1.3:1:2:
2.
4. The method for preparing a Cr2AlC-derived two-dimensional carbide material according to claim 2, characterized in that: In the step (2), the molar ratio of Cr2AlC to copper chloride, sodium chloride and potassium chloride is 1:1.5-6:1:
1.
5. The method for preparing a Cr2AlC-derived two-dimensional carbide material according to claim 2, characterized in that: In the step (2), the heating rate at a temperature above 300° C. is 2 to 5° C. / min, the high reaction temperature is 600 to 700° C., and the reaction time is 3 to 9 hours.
6. The method for preparing a novel Cr2AlC-derived two-dimensional carbide material according to claim 2, characterized in that: The concentration of the FeCl3 solution used in step (2) is 0.5-1 mol / L.
Citation Information
Cited By
MAX series material with cross-scale geometric structure and template-oriented preparation method of MAX series material
CN122464422A
